THE STUDY OF THE IMPACT OF LANGUAGE CONTACT ON PHONOLOGICAL SYSTEMS (International Journal of Food and Nutritional Sciences, 2022)
Language contact, the interaction between speakers of different languages, has long beenrecognized as a catalyst for linguistic change, particularly in phonological systems. Thisresearch paper examines how language contact influences phonological systems throughprocesses such as borrowing, convergence, and diffusion.